The complex epistemological challenge of data curation in dietary metabarcoding: Comment on "The precautionary principle and dietary DNA metabarcoding: Commonly used abundance thresholds change ecological interpretation" by Littleford‐Colquhoun et al. (2022). Issue 22 (2nd July 2022) - Tercel, Maximillian P. T. G.; Cuff, Jordan P.
Abstract: In their article, Littleford‐Colquhoun et al. (2022) advise against using arbitrary relative read abundance (RRA) thresholds (i.e., minimum sequence copy thresholds) for removing low‐abundance sequences since they can increase false negative rates in dietary DNA metabarcoding data sets. The main criticisms presented against these widespread methods are that they (i) are arbitrary, often existing as standard values or defined based on researcher‐selected delineations, (ii) are subjective, varying between studies and contexts, and, most problematically, (iii) result in the exclusion of true positives, particularly rarely consumed taxa, to the detriment of ecological insight. We commend the authors for presenting a refreshing and timely perspective on this often neglected topic, which is certainly in need of greater discussion following over a decade of significant advances in dietary metabarcoding. In this complex epistemological problem of false positives versus false negatives, we feel that several of the points raised deserve additional discussion. We address these aspects below, including measured approaches to data filtration and consistent representation of RRAs, and we welcome any further discourse to solidify or refute the concepts therein.